Rethinking Marital Love: From Sexual Relations to Conjugal Relationality (Hekima Review, 2016)
The amount of love dosage diagnosed in the world is enough to remedy the incurable heartbreaks, unfaithfulness and high rate of divorce which nag contemporary marital love. Though, it seemed to have been perceived in an irresistible seductive fragrance, in reality, the current manifestation of love chokes. Hedonism rejuvenates in full flesh, love is reduced to sex and humanity to pleasure machines. Thus, these call for urgent need to rethink love in order that it may better lead the world towards a salvific comprehension of Marital Love. The latter without excluding sex builds primarily on the principle of triadic relationality such that, Marital Love transcends any pure egocentric or altruistic understanding of love, but is aptly grasped in its fundamental character of transcendence - God who is love